Coping with Regional Inequality in Sweden: Structural Change, Migrations and Policy, 1860-2000 - Kerstin Enflo; Joan Ramón Rosés (European Historical Economics Society (EHES), 2012)
In many countries, regional income inequality has followed an inverted U-shaped curve, growing during industrialisation and market integration and declining thereafter. By contrast, Sweden's regional inequality dropped from 1860 to 1980 and did not show this U-shaped pattern. Accordingly, today's regional income inequality in Sweden is lower than in other European countries. We note that the prime mover behind the long-run reduction in regional income differentials was structural change, whereas neo-classical and technological forces played a relatively less important role. However, this process of regional income convergence can be divided into two major periods. During the first period (1860-1940), the unrestricted action of market forces, particularly the expansion of markets and high rates of internal and international migrations, led to the compression of regional income differentials. In the subsequent period (1940-2000), the intended intervention of successive governments appears to have also been important for the evolution of regional income inequality. Regional convergence was intense from 1940 to 1980. In this period, governments aided the convergence in productivity among industries and the reallocation of the workforce from the declining to the thriving regions and economic sectors. During the next period (1980-2000), when regional incomes diverged, governments subsidised firms and people in the declining areas.
Keywords: N94; N93; R11; R12; 330; Convergence; regional policy; neo-classical growth model; labour reallocation